A Review of Energy Storage Mechanisms in Aqueous Aluminium Technology - N. Melzack; R. G. A. Wills (Frontiers in Chemical Engineering, 2022)
This systematic review covers the developments in aqueous aluminium energy storage technology from 2012, including primary and secondary battery applications and supercapacitors. Aluminium is an abundant material with a high theoretical volumetric energy density of –8.04 Ah cm−3. Combined with aqueous electrolytes, which have twice the ionic storage potential as non-aqueous versions, this technology has the potential to serve many energy storage needs. The charge transfer mechanisms are discussed in detail with respect to aqueous aluminium-ion secondary batteries, where most research has focused in recent years. TiO2 nanopowders have shown to be promising negative electrodes, with the potential for pseudocapacitive energy storage in aluminuim-ion cells. This review summarises the advances in Al-ion systems using aqueous electrolytes, focusing on electrochemical performance.